N-[2-(Diphenylphosphanyl)benzylidene]-4-methylaniline - Malik, Abdul (JURNAL VARIASI, 2011)
The title compound, C26H22NP, is a Schiff base derived from triphenylphosphine with a 4-methylphenylamine group attached to one of the benzene rings of the phosphine in the o-position. The azomethine C N bond length is 1.259 (3) Ã and the dihedral angle between the benzene ring and its 4-methylphenylamine substituent is 40.02 (2) Ã . The geometry at the P atom is approximately tetrahedral.